Pengaruh Pelayanan Dan Inovasi Produk Terhadap Kepuasan Pelanggan Pada Usaha Toko Emas Di PD Pasar Jaya Cengkareng: The Effect of Service and Product Innovation on Customer Satisfaction in Gold Shops at PD Pasar Jaya Cengkareng - Adriana Holo; Ratih Hastasari; Wawan Saputra (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstract - This study aims to analyze the effect of service quality and product innovation on customer satisfaction at a gold shop business in PD Pasar Jaya Cengkareng. The research background highlights the importance of service quality and product innovation as strategies to maintain satisfaction and build customer loyalty in the increasingly competitive traditional market. The study employed a quantitative descriptive approach. The sample consisted of 100 active customers selected using purposive sampling, with the majority aged 30–39 years. Data were collected through a questionnaire using a five-point Likert scale, with SERVQUAL indicators (tangible, reliability, responsiveness, assurance, empathy) for the service variable, and design, variety, customization, and aesthetics for the product innovation variable. Data were analyzed using SPSS version 27 through validity testing, reliability testing, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results showed that service quality had a positive and significant effect on customer satisfaction with a t-count of 8.190 > t-table 1.984. Product innovation also had a significant effect with a t-count of 11.468 > t-table 1.984. Simultaneously, both variables significantly affected customer satisfaction with an F-count of 190.982 > F-table 3.09, and a combined contribution of 79.7%. These findings emphasize the importance of improving responsive and professional services, as well as developing product designs aligned with market trends to sustain satisfaction and long-term loyalty